Influence of polyphenol rich seabuckthorn berries juice on release of polyphenols and colonic microbiota on exposure to simulated human digestion model. (September 2018) - Attri, Sampan; Goel, Gunjan
Abstract: The present study investigated the effect of polyphenol rich Sea buckthorn berries juice (SBJ) on colonic microbial composition and diversity using in vitro simulated gut model. The release of polyphenols, their antioxidant activity and impact on microbial diversity was evaluated under long term fermentation for 21 days. The treatment of colonic reactors with basal feed supplemented with SBJ resulted in an increase in population and diversity of beneficial bacteria as revealed by viable cell count and PCR-DGGE. A higher release of phenolics was observed, which resulted in higher antioxidant activity in the colonic reactors throughout the treatment period (p < 0.05). Higher content of resveratrol, rutin and chlorogenic acid were observed in ascendens colon whereas quercetin, ferulic and caeffic acid level were higher in descendens colon due to biotransformation of polyphenols in the later part of colon. The Principal Component Analysis also indicated the stimulatory effect of SBJ on the beneficial microbial population of Lactobacilli, Bacteroides/Prevotella and Bifidobacteria in all the three reactors. It also confirmed higher release of polyphenolic compounds and associated antioxidant activities in descendens colon. Graphical abstract: Unlabelled Image Highlights: Seabuckthorn berry juice was evaluated under simulated gut environment. Simulation resulted in release of higher phenolic content and associated antioxidant activities. Juice possessed prebiotic activities as it results in proliferation of target beneficial group of organisms. Biotransformation and metabolism of polyphenols in the colon reactors was also observed. Stable, adapted gut microbial communities were observed during washout period without any supplementation.